2015
DOI: 10.1097/md.0000000000001660
|View full text |Cite
|
Sign up to set email alerts
|

Risk-Factor Profile and Comorbidities in 2398 Patients With Newly Diagnosed Hypertension From the Abuja Heart Study

Abstract: Risk factors, comorbidities, and end-organ damage in newly diagnosed hypertension (HT) are poorly described in larger cohorts of urban African patients undergoing epidemiological transition. We therefore decided to characterize a large cohort of hypertensive subjects presenting to a tertiary health center in sub-Saharan Africa.It is an observational cross-sectional study. We prospectively collected detailed clinical, biochemical, electrocardiography, and echocardiography data of all subjects with HT as the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Similar to previous studies, (17) our female hypertensive patients had significantly higher body mass index and LDL cholesterol.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to previous studies, (17) our female hypertensive patients had significantly higher body mass index and LDL cholesterol.…”
Section: Discussionsupporting
confidence: 91%
“…The higher recruitment and hypertension control rates of female participants in hypertension studies in Africa has been shown in large population hypertension registries in Africa [16,17]. Potential reasons for these differences between sexes include earlier detection of hypertension in women at both antenatal and postnatal cares, and higher health-seeking behaviors in African women compared with men.…”
Section: Results In Contextmentioning
confidence: 99%
“…In addition, 5 or 10 mg nebivolol resulted in response rates of >55%. These findings are of clinical importance, especially because of the excessive burden of hypertension and its complications and the low rates of blood pressure control in sub-Saharan Africa (2,16). The results imply that beta-1-selective beta-blockers like nebivolol apart from being used as monotherapy in grade 1 hypertension could be the fourth class of medication to be considered after maximum doses of a combination of long-acting calcium channel blockers, thiazide diuretics and renin-angiotensin-aldosterone blockers have been (6.90, 9.30) used in this population group.…”
Section: Discussionmentioning
confidence: 99%
“…Although hypertension affects every racial group, complications such as heart failure, chronic kidney disease and cerebrovascular accidents are more prevalent in the Black population ( 1 ). For example, in the Abuja Heart Study, about seventy-five percent (75%) of hypertensive patients presenting de novo to a tertiary healthcare institution had one or more complications on presentation ( 2 ). In addition, there is substantial clinical evidence indicating that monotherapy with beta-blockers, angiotensin converting enzyme inhibitors and angiotensin receptor blockers are less effective in reducing blood pressure among hypertensive Black patients compared to Whites ( 3 5 ).…”
Section: Introductionmentioning
confidence: 99%